Researching Together: Exploring Research Productivity and Collaboration of Librarians in ASEAN Countries. Issue 3 (3rd July 2018) - Ramos-Eclevia, Marian; Janio, Rizalyn V.; Vinzon, Minette R.; Eclevia, Carlos L.; Apolinario, Rhea Rowena U.
ABSTRACT: This study employs bibliometrics to examine the research productivity and patterns of collaboration of librarians in the Association of Southeast Asian Nations (ASEAN) countries. All articles, conference papers, book chapters, and reviews in the LIS field written by librarians from ASEAN countries between 2001 and 2016 indexed by Scopus and Web of Science were extracted. Research publications were analysed in terms of productivity by country and institutions, authorship and collaboration patterns, document types, subject categories and publication year. While many of the librarians had conducted research as a requirement for their bachelor and/or master degree in Library and Information Science (LIS), research writing and knowledge sharing through publishing and paper presentation in conferences were not prevailing research activities. Librarians from Malaysia were the most productive authors in this dataset. Many of the scholarly works were single authored. Therefore, the degree of collaboration between authors was quite low. Likewise, the growth rate of research collaboration cannot be predicted from this data. This study provides recommendations to encourage ASEAN librarians to actively engage in research not just for personal benefits, but also to advance the librarianship as a profession.